2010
DOI: 10.1093/pasj/62.1.1
|View full text |Cite
|
Sign up to set email alerts
|

A New Set of Variables in the Three-Body Problem

Abstract: We propose a set of variables of the general three-body problem both for two-dimensional and three-dimensional cases. The variables are ($\lambda, \theta, \Lambda, \Theta, k, \omega$), or equivalently ($\lambda, \theta, L, \dot{I},k,\omega)$ for the two-dimensional problem, and ($\lambda, \theta, L, \dot{I}, k, \omega, \phi, \psi$) for the three-dimensional problem. Here, ($\lambda, \theta$) and ($\Lambda, \Theta)$ specify the positions in the shape spheres in the configuration and momentum spaces, $k$ is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Actually, Hsiang and Straume [4,5], Chenciner and Montgomery [1], Montgomery [9] and Mockel [7] showed that this metric space is the 'shape sphere' and the distance ( 27) is the distance on the shape sphere. Kuwabara and Tanikawa also noted that the shape sphere is useful to investigate the equal-mass free-fall problem [6,12]. The map (25) makes the shape sphere 2π/3 rotation around the axis that connects the two Lagrange points.…”
Section: Invariantsmentioning
confidence: 99%
“…Actually, Hsiang and Straume [4,5], Chenciner and Montgomery [1], Montgomery [9] and Mockel [7] showed that this metric space is the 'shape sphere' and the distance ( 27) is the distance on the shape sphere. Kuwabara and Tanikawa also noted that the shape sphere is useful to investigate the equal-mass free-fall problem [6,12]. The map (25) makes the shape sphere 2π/3 rotation around the axis that connects the two Lagrange points.…”
Section: Invariantsmentioning
confidence: 99%
“…This sphere is exactly the Riemann sphere of the complex plane x + iy. This fact was first noticed by George Lemaître [12] and used by Hsiang and Straume [9,10], Chenciner and Montgomery [2], Montgomery and Mockel [16], Kuwabara and Tanikawa [11].…”
Section: Does This Motion Satisfy the Equation Of Motion?mentioning
confidence: 88%
“…To describe the motion in shape, we used the shape variable ζ ∈  in equation (11), or η ∈  in equation ( 15), introduced by Moeckel and Montgomery. We wrote the Lagrangian in the size variable r, the rotation variable ϕ, and the shape variable η.…”
Section: Summary and Discussionmentioning
confidence: 99%